Clonal Growth Forms in Eastern Ladakh, Western Himalayas: Classification and Habitat Preferences - Klimešová, J. (Jitka); Doležal, J. (Jiří); Dvorský, M. (Miroslav); de Bello, F. (Francesco); Klimeš, L. (Leoš) (Folia Geobotanica, 2011)
Earlier observations that plant clonality, i.e., production of potentially independent offspring by vegetative growth, increase in importance in cold climates such as in arctic and alpine regions, have been recently questioned. However, lack of data obtained using a comparable methodology throughout different regions limit such comparisons. Here we present a classification of clonal growth forms for vascular plants from East Ladakh (an arid mountain range in NW Himalaya, India), and assess the relationship of these forms with multiple environmental gradients. Based on field assessment of clonality in 540 species we distinguished 20 growth forms, which were then grouped into four broader space occupancy strategies. Occurrence in communities and relationship with environmental characteristics and altitude were analyzed using multivariate methods.